Employee Participation in Decision Making in RMG sector of Bangladesh: Correlation with Motivation and Performance (Journal of Business and Technology (Dhaka), 2012)
Participation in decision making in industry results in satisfaction of employees and an increase in productivity and profit. It empowers the employer to achieve the organizational goal. This study was conducted to assess the present situation, nature and types of workers participation and motivation system in Ready Made Garments (RMG) sector of Bangladesh. The study identifies the causes of poor participation of the employees in decision making and correlate between employee participation, motivation and performance. The study revealed that there is a significant positive correlation between decision making, motivation and performance. The study also identified five major causes of poor participation in decision making, such as, absence of willingness of the management, absence of labor union activities, lack of workforce diversity, illiteracy of the workers and political grouping among the workers.DOI: http://dx.doi.org/10.3329/jbt.v5i2.9984Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 122-132